2016
DOI: 10.1080/01446193.2016.1237776
|View full text |Cite
|
Sign up to set email alerts
|

Does the built-environment industry attract risk-taking individuals?

Abstract: This exploratory research examines whether or not those attracted to professional-level occupations in the built-environment industry are innately physical risk-takers and hence potentially, thereby, more likely to countenance or contribute to physically risky workplace climates. Using individual-level data, the occupational attractiveness of the built-environment industry subsectors of construction management and architecture are each found positively and significantly to be predicted by physical risk-taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…A study performed among 904 workers in an academic health center in the United States of America in 2000 showed a lifetime rate for problem and pathologic gambling of 3.0% and 1.8% respectively 20) . Phua has shown that occupational attractiveness of the profession of banking is predicted by gambling 21) . A French nationwide cross-sectional study performed in 2010 has shown that teachers were less likely to gamble regularly (OR [95%CI]=0.41 [0.25-0.68]) 22) .…”
Section: Introductionmentioning
confidence: 99%
“…A study performed among 904 workers in an academic health center in the United States of America in 2000 showed a lifetime rate for problem and pathologic gambling of 3.0% and 1.8% respectively 20) . Phua has shown that occupational attractiveness of the profession of banking is predicted by gambling 21) . A French nationwide cross-sectional study performed in 2010 has shown that teachers were less likely to gamble regularly (OR [95%CI]=0.41 [0.25-0.68]) 22) .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Safe Work Australia (2015) found that construction workers were more likely than workers in other industries to agree that taking risks was a normal part of their daily work, that their workplace does not suit those overly concerned about risk, that risk taking at work is acceptable, especially if it means getting the project finished on time. More recently, Phua's (2017) comparative research into the risk-taking propensity of professionals who work in construction also found that the construction industry is attractive to physical risk-takers, which she argues has important implications for safety performance in the industry. The importance of sex as a form of masculine identity in our results also reflects recent research by Datta (2009), Farrell (2010), Rumens (2013), Chan (2013), Wright (2013) and Galea et al (2017) which has provided ethnographic and other empirical evidence of overt sexuality, sexual story-telling, vulgar sexual behaviour and joking and even sexual harassment at play in construction site interactions between men, and men and women.…”
Section: Resultsmentioning
confidence: 99%
“…In CM, such studies are drawing more scholarly attention in recent years (e.g. Toor and Ofori 2009;Phua, 2017). Similarly, for the purpose of testing the propositions here, such an approach is useful for shedding light on our understanding of how and why different internal procedures/processes of organizational climates (e.g.…”
Section: Methodological Possibilitiesmentioning
confidence: 98%
“…As the sustainability agenda gathers pace in recent years (e.g. Department of Business, Enterprise andRegulatory Reform 2008, Department for Business, Energy andIndustrial Strategy, 2013), so does the amount of research aimed at exploring the factors that either promote or inhibit it at regional, national and even international levels (Department for Environment, Food & Rural Affairs, 2010-2017United Nations, 2015). In the construction management (CM) and building disciplines, the majority of this work is centred on the technical, economic and policy aspects (e.g.…”
Section: Introductionmentioning
confidence: 99%